Storage root yield response to leaf harvest of improved and local cassava varieties in DR Congo - Hauser, S.; Bakelana, Z.; Bungu, D.; Mwangu, K.; Ndonda, A. (Informa UK Limited, 2021)
Although cassava is usually grown for its starchy roots, cassava leaves are an important vegetable and protein source in sub-Saharan countries. Eleven cassava mosaic disease (CMD) tolerant and two susceptible varieties were planted in six trials; leaves were harvested at 4, 8 and 11 months after planting (MAP) and storage roots were harvested at 12 MAP. Edible leaf and storage root dry matter yields were strongly affected by variety and interacted with location. Edible leaf yields ranged from 209 to 435 kg ha−1 DM among varieties. Storage root yields ranged from 2540 to 9250 kg ha−1 DM among locations and from 2470 to 7550 kg ha−1 among varieties. Leaf harvest caused 15.8% storage root yield loss. Susceptible varieties produced lowest edible leaf (209 kg ha−1) and storage root (2530 kg ha−1) yields in all locations. Improved varieties suffered storage root yield reductions of 5–25.8%, equivalent to 400–1550 kg ha−1. Edible leaf yield and storage root yield were not correlated. Variety TME419 produced the highest average storage root yields in 3 of 6 locations. The three best leaf producing varieties were not among the best storage root producers, indicating an incompatibility of the two production objectives.